Facilitator's guide to participatory decision-making - Kaner, Sam...[et al.] (New Society Pub. British ColombiaUS, 2000)
Presents 3 fundamental principles of participatory decision-making, namely: dynamics of group decision making; participatory decision-making core values; and the role of the facilitator. Looks in depth at a number of process management skills including: facilitative listening skills such as paraphrasing and mirroring; techniques for facilitating an open discussion; alternatives to the open discussion; and, brainstorming. Introduces several tools for building sustainable agreements.